Bactericidal effect of ultrasound-responsive microbubbles and sub-inhibitory gentamicin against Pseudomonas aeruginosa biofilms on substrates with differing acoustic impedance - Plazonic, F; LuTheryn, G; Hind, C; Clifford, M; Gray, M; Stride, E; Glynne-Jones, P; Hill, M; Sutton, JM; Carugo, D (Elsevier, 2022)
The aim of this research was to explore the interaction between ultrasound-activated microbubbles (MBs) and Pseudomonas aeruginosa biofilms, specifically the effects of MB concentration, ultrasound exposure and substrate properties on bactericidal efficacy. Biofilms were grown using a Centre for Disease Control (CDC) bioreactor on polypropylene or stainless-steel coupons as acoustic analogues for soft and hard tissue, respectively. Biofilms were treated with different concentrations of phospholipid-shelled MBs (107–108 MB/mL), a sub-inhibitory concentration of gentamicin (4 µg/mL) and 1-MHz ultrasound with a continuous or pulsed (100-kHz pulse repetition frequency, 25% duty cycle, 0.5-MPa peak-to-peak pressure) wave. The effect of repeated ultrasound exposure with intervals of either 15- or 60-min was also investigated. With polypropylene coupons, the greatest bactericidal effect was achieved with 2 × 5 min of pulsed ultrasound separated by 60 min and a microbubble concentration of 5 × 107 MBs/mL. A 0.76 log (83%) additional reduction in the number of bacteria was achieved compared with the use of an antibiotic alone. With stainless-steel coupons, a 67% (0.46 log) reduction was obtained under the same exposure conditions, possibly due to enhancement of a standing wave field which inhibited MB penetration in the biofilm. These findings demonstrate the importance of treatment parameter selection in antimicrobial applications of MBs and ultrasound in different tissue environments.